2014
DOI: 10.5539/jsd.v7n6p46
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Factors that Predict Energy Conservation: The Theory of Planned Behavior and Beliefs about Climate Change

Abstract: A survey of college students was used to examine predictors of four types of energy conservation behavior. Our proposed predictors were derived from Ajzen's Theory of Planned Behavior (TPB) and from problem awareness variables (environmental concern, and knowledge and beliefs about global warming) thought to have indirect effects on conservation via TPB constructs. TPB constructs were significant direct predictors of target behaviors. Perceived behavioral control (PBC) was the strongest and most consistent pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…This finding is supported by Abrahamse and Steg (), Clement et al . (), Chen and Knight, (2014), and Gao et al . () who found SN insignificant and that it has the weakest relationship with behavioural intentions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding is supported by Abrahamse and Steg (), Clement et al . (), Chen and Knight, (2014), and Gao et al . () who found SN insignificant and that it has the weakest relationship with behavioural intentions.…”
Section: Discussionmentioning
confidence: 95%
“…This buttress what is previously known that PBC is the strongest predictor and is found to have a positive influence on electricity conservation intentions (Ma et al ., ; Clement et al . (). Once individuals have high control over their electricity consumption practices, the greater indication is that they will exhibit energy‐conservation behaviours (Oikonomou et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…Axelrod and Lehman (1993, p. 149) argued that environmental concern helps to better understand the range of factors that influence an individual’s choice regarding different environmentally responsible behaviors. Particular to the TPB, several studies have found that TPB variables have the potential to mediate the relationship between environment concern and resultant behaviors or behavioral intentions in studies examining public transportation (De Groot & Steg, 2007) and reduced energy use in the home (Clement, Henning, & Osbaldiston, 2014). In general, consumers who have a high level of environmental concern tend to be more involved in environmental issues (Lee, 2008), and this involvement plays a significant role in influencing the effectiveness of message framing (Maheswaran & Meyers-Levy, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, psychological theories were included, such as the TPB (Ajzen, ), and behavioural economic theories, such as the prospect theory (Kahneman and Tversky, ). These theoretical frameworks have been adopted in consumer studies by investigating individual climate‐friendly behaviours, such as green consumption (Lin, ) and household energy savings (Clement et al ., ), as well as individual climate adaptation (Botzen and van den Bergh, ).…”
Section: Resultsmentioning
confidence: 97%
“…Clement et al . () surveyed college students to investigate the role of subjective norms and PBC in driving the adoption of climate‐friendly behaviours, while also accounting for students' concerns, knowledge and beliefs about climate change. Lin () complemented TPB with the perceived benefit or cost dimension, measuring individual beliefs about the gains or losses produced by a given action, while investigating Taiwanese households' intention to purchase energy‐efficient appliances.…”
Section: Resultsmentioning
confidence: 99%